The implications for the informal sector of European Union integration - WINDEBANK, Jan; WILLIAMS, Colin C. (European Spatial Research and Policy, 1995)
This article explores the implications of European Union (EU) integration for the informal sector. Using evidence from numerous empirical studies of individual localities throughout · he EU, the informal sector is revealed to rei n force the disparities produced by the formal sector. In consequence, any increase in inequalities in the formal sphere resulting from the Single European Market will be accentuated by the informal sector. Since further state spending on social provision at EU or national level is unlikely, for social progress and justice to be achieved, we advocate the harnessing of the informal sector in order to meet welfare needs, particularly of those groups and areas marginalised from the employment sphere.